2018
DOI: 10.1161/jaha.117.008089
|View full text |Cite
|
Sign up to set email alerts
|

DASH Score and Subsequent Risk of Coronary Artery Disease: The Findings From Million Veteran Program

Abstract: BackgroundWhile adherence to healthful dietary patterns has been associated with a lower risk of coronary artery disease (CAD) in the general population, limited data are available among US veterans. We tested the hypothesis that adherence to Dietary Approach to Stop Hypertension (DASH) food pattern is associated with a lower risk of developing CAD among veterans.Methods and ResultsWe analyzed data on 153 802 participants of the Million Veteran Program enrolled between 2011 and 2016. Information on dietary hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…[33][34][35] Similarly, the aHEI and DASH diet are associated with reduced mortality and lower rates of several chronic diseases. [9][10][11][12][13][14][15] A healthy diet is also associated with concomitant positive lifestyle factors, such as those seen in our study: less smoking and increased physical activity, both of which are associated with a lower risk of frailty. 1 Because weekly vigorous exercise was included in the frailty index as a proxy for physical inactivity, we did not examine it as a potential confounder.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[33][34][35] Similarly, the aHEI and DASH diet are associated with reduced mortality and lower rates of several chronic diseases. [9][10][11][12][13][14][15] A healthy diet is also associated with concomitant positive lifestyle factors, such as those seen in our study: less smoking and increased physical activity, both of which are associated with a lower risk of frailty. 1 Because weekly vigorous exercise was included in the frailty index as a proxy for physical inactivity, we did not examine it as a potential confounder.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, the Dietary Approaches to Stop Hypertension (DASH) score has not been evaluated in terms of its relationship with frailty, despite being associated with lower chronic disease and mortality risk. 10,12,14,15 In this study, we sought to investigate the relationship between self-reported diet quality, measured using three different dietary indices, the aHEI, the DASH dietary assessment, and the MDS, with frailty. We hypothesized that better diet quality would be associated with lower odds of being pre-frail and frail, using two common methods of measuring frailty.…”
mentioning
confidence: 99%
“…In a recent longitudinal study of 153,082 US veterans, the DASH diet score was inversely associated with the incidence of coronary artery disease (HR 0.82, 95% CI 0.75–0.89). [ 27 ] Likewise, Niknam et al analyzed the data of 388 hospitalized patients in a case-control study, and found that a DASH-style diet could lower the prevalence of stroke (odds ratio [OR] 0.48, 95% CI 0.24–0.96). [ 28 ] Apart from this, a previous meta-analysis by Salehi-Abargouei et al [ 29 ] also reported an inverse relationship between DASH diet consumption and risk of stroke (RR 0.81, 95% CI 0.72–0.92).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of cohort studies revealed a linear and inverse association between DASH diet intake and the risks of coronary artery disease, stroke and heart failure (18,19) . Recent analyses confirm the cardioprotective effects of high adherence to the DASH diet that was associated with the lower risk of specific cardiovascular events (coronary artery disease and stroke), total incident cardiovascular events and also CVD-related death (20,21) .…”
mentioning
confidence: 89%